PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 009 BINIO JAYA KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Aris Setia Ningsih; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted because of the expected learning outcomes IPS has not reached KKM set by the school 70. It is necessary for research with the aim to improve the learning outcomes of students of class V SDN 009 Binio Jaya 2014/2015 school year by implementing inquiry learning model that held on 11, 18, March 25, 2015 in the first cycle and the 1st, 8th, April 15, 2015 for the second cycle. The subjects were students of class V SDN 009 Binio Jaya, amounting to 25. The results showed that the activity of teachers and students has increased. The percentage of teachers in the first cycle activities 1 meeting that is 66.6% with enough categories, meeting 2 is 80.55% with the good category, while in the first meeting of the second cycle is 69.45% with the good category, meeting 2 is 86.12% with both categories. The percentage of student activity in the first cycle of meeting 1 is 6.48% with enough categories, namely 9% 2 meetings with both categories, while the second cycle 1 meeting, namely 10,08% with the good category, meeting 2 is 77.28% with both categories. Furthermore, the study results an increase of the average value. On the basis of the average score value of 52.80 with classical completeness 40% (not complete), increased in the first UH average value is 65.20 with classical completeness 72% (not finished) and UH II, namely 74.40 with thoroughness classical 80% (completed). The final conclusion is that the application of the inquiry model can improve learning outcomes students of class V at elementary school 009 Binio Jaya.Keywords: inquiry model, the results of social studies